Second language acquisition: students’ vocabulary size and their strategies for Retaining It - Puteri, Celiacika Gustisiwi (Universitas Lampung, 2022)
The success of the second language acquisition by students is determined by the second language vocabulary mastery as vocabulary is the words that make up a language. The present study aimed at investigating the vocabulary mastery level and vocabulary learning strategies of students majoring in English. The participants were 46 students of the third-year English Education Department at the University of Lampung for the 2020/2021 academic year. This study applied a descriptive quantitative research design, with data collection instruments of test and questionnaire. A vocabulary size test was utilized to identify the students’ vocabulary mastery level. Meanwhile, the questionnaire was employed to explore the learning strategies used by the students to enhance and retain their vocabulary knowledge. The researcher analyzed the data statistically and then described the data so that a reliable finding could be obtained. The results revealed that most English Education Department students at the University of Lampung were above the median vocabulary mastery level. Furthermore, in learning vocabulary, using English media was the most preferred strategy, while talking to a native speaker is the least used strategy by the students.Keywods: Second language acquisition, vocabulary mastery, vocabulary learning strategies, vocabulary size.